Nonalcoholic Fatty Liver Disease and Sarcopenia: Where Do We Stand? - Ivana Mikolasevic; Tajana Pavic; Tajana Filipec Kanizaj; Darija Vranesic Bender; Viktor Domislovic; Zeljko Krznaric (Canadian Journal of Gastroenterology and Hepatology)
The link between metabolic syndrome (MetS) and sarcopenia has not been extensively studied, but it is evident that they share several common features. Crucial mechanisms involved in sarcopenia-nonalcoholic fatty liver disease (NAFLD) interplay are based on effects of insulin resistance, chronic inflammation, oxidative stress, and crosstalk between organs by secretion of cytokines (hepatokines, adipokines, and myokines). Currently, published studies confirm the association of sarcopenia with the degree of NAFLD defined by liver histology. However, prospective studies that will give us information regarding the causal effect of NAFLD and sarcopenia are still needed. Furthermore, there is a need for a patient-friendly, noninvasive, low-cost method for detection of loss of skeletal muscle mass, strength, and physical performance in the context of NAFLD. Moreover, potential treatment strategies such as physical exercise and nutritional supplementation, that are usually a part of management of sarcopenia, should also be investigated in NAFLD patients, especially given the fact that for now, we do not have a good treatment option for NAFLD. Therefore, future investigations should combine studies on NAFLD and sarcopenia in terms of physical activity and nutritional interventions such as vitamin D supplementation. This review aims to report recent evidence concerning the links between sarcopenia and NAFLD and methods to assess sarcopenia.